Uniqueness for an inverse space-dependent source term in a multi-dimensional time-fractional diffusion equation. (November 2016) - Wei, Ting; Sun, Liangliang; Li, Yushan
Abstract: This paper is devoted to identify a space-dependent source term in a multi-dimensional time-fractional diffusion equation from boundary measured data. The uniqueness for the inverse source problem is proved by the Laplace transformation method.